Analisis Ragam Bahasa Willy The Kid di Platform X - Hermanto, Aqilla Attaya Putri; Damayanti, Alika Devina; Salsabilla, Amelda Ari; Terra, Elian Angkasa; Sholihatin, Endang; Putri, Suwandari; Marsanda, Venisia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The use of slang language in criminal communication reflects an understanding of language and can help in analyzing and identifying various languages and the presence of criminal content in language. This research method uses qualitative descriptive methods. The results of this study indicate that, 1) The language used in Willy The Kid's tweets, a user on platform X, is informal, and (2) in Willy The Kid's tweets on platform X, there is criminal content in language, namely incitement, hate speech, and insults. This informal language variety is characterized by the use of non-standard words and expressions, as well as the use of slang. The use of informal language variety can be interpreted as Willy The Kid's efforts to build a close relationship with his audience.